Epizootic Activity of the Central Caucasian High-Mountain Natural Plague Focus - A. N. Kulichenko; Yu. M. Evchenko; G. A. Mozloev; M. P. Grigor'ev; L. V. Lyapustina; N. V. Churikova (Проблемы особо опасных инфекций, 2011)
Analysis of the long-term data made it possible to identify three periods of epizootic activity of the Central Caucasian high-mountain natural plague focus against the background of the overall downward trend. In the third period (2000-2010) the focus was shown to be under the intense negative influence of natural and anthropogenic factors that stipulated its depression. The natural factors were weather conditions unfavorable for life-sustaining activity of mountain ground-squirrels, the main plague carriers in this focus. Anthropogenic pressure over the focus manifested as follows. The quantity of cattle decreased, that resulted in decrease of territories of the mountain pasturelands, the natural habitats of mountain ground-squirrels. As areas suitable for life-sustaining activity of the mountain ground-squirrel populations reduced, the number of their settlements declined. With account taken for the effect of the anthropogenic influence stated above, short-term and medium-term prognoses of epizootic activity of Central Caucasian high-mountain natural plague focus indicate of rare non-intensive epizooties.